Control of Green Mold and Sour Rot in Mandarins by Postharvest Application of Natamycin and an Allium Extract - Pérez Faggiani, Elena; Fernandez, Gerónimo; Cocco, Mariángeles; Sbres, Mauricio; Blanco, Oribe; Lado, Joanna (MDPI, 2024)
The efficacy of natamycin (Fruitgard Nat 20) and Proallium (an extract of allium including propyl thiosulfinate oxide (PTSO)) against sour rot and green mold in mandarins was evaluated under controlled and commercial conditions. The study involved artificial inoculation of Nova, Tango, Orri, Afourer, Murcott, and Nules Clementine mandarins with isolates of Penicillium digitatum resistant to imazalil and pyrimethanil and an isolate of Geotrichum citri-aurantii susceptible to propiconazole fungicides. Under laboratory conditions, natamycin applied at 1500 µg mL−1 significantly reduced green mold by 61.2% in Orri and sour rot by 62.8% in Nova and 80% in Tango. Increasing the concentration to 2000 µg mL−1 further improved control of sour rot in Nova to 92.8%. In commercial trials, natamycin at 1500 µg mL−1 was ineffective on Afourer; however, 2000 µg mL−1 reduced sour rot by 39% on Nules Clementine. Proallium (12–16 µg mL−1 PTSO) applied under controlled conditions effectively reduced green mold by 33% in Nova and 31% in Nules Clementine, and sour rot by 19%, 41%, and 36% in Nules Clementine, Nova, and Afourer, respectively. Under commercial conditions, using the same dose of Proallium, there was a 51.5% reduction in the incidence of imazalil and pyrimethanil-resistant P. digitatum strains and a 36.5% reduction in sour rot. Both natamycin and PTSO showed promising results for managing green mold caused by fungicide-resistant strains, but further research is needed to optimize control of sour rot in mandarins.